2014
DOI: 10.1073/pnas.1324235111
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell FGF signaling is required for injury response but not for vascular homeostasis

Abstract: Endothelial cells (ECs) express fibroblast growth factor receptors (FGFRs) and are exquisitely sensitive to FGF signals. However, whether the EC or another vascular cell type requires FGF signaling during development, homeostasis, and response to injury is not known. Here, we show that Flk1-Cre or Tie2-Cre mediated deletion of FGFR1 and FGFR2 (Fgfr1/2Flk1-Cre or Fgfr1/ 2 Tie2-Cre mice), which results in deletion in endothelial and hematopoietic cells, is compatible with normal embryonic development. As adults,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 48 publications
3
107
1
1
Order By: Relevance
“…S5, B and C). In agreement with a previous study (19), Fgfr1 ECKO mice appeared normal. In particular, there was no delay in the formation of retinal vasculature in P6 pups and adults ( fig.…”
Section: Endothelial Cell-specific Deletion Of Fgfr1 Enhances Endmt Isupporting
confidence: 93%
“…S5, B and C). In agreement with a previous study (19), Fgfr1 ECKO mice appeared normal. In particular, there was no delay in the formation of retinal vasculature in P6 pups and adults ( fig.…”
Section: Endothelial Cell-specific Deletion Of Fgfr1 Enhances Endmt Isupporting
confidence: 93%
“…Experiments performed on FGFR1 and FGFR2 null mice in both endothelial and hematopoietic cells indicate that these receptors are not required for vascular homeostasis or physiological functions. However, FGFR signalling in endothelial cells plays a pivotal role in tissue repair and neovascularization following injury, pointing to endothelial cell FGFRs as a target for the therapy of diseases characterized by an aberrant vascular proliferation [41].…”
Section: The Fgf/fgfr System In Endothelial Cellsmentioning
confidence: 99%
“…Systemic administration of soluble dominant negative FGFR1 decreased VEGFR2 expression and impaired post-ischemic neovascularization. Recently, studies with endothelial and hematopoietic-specific deletion of Fgfr1 and Fgfr2 revealed that Fgfr1 and Fgfr2 are dispensable for normal vascular development; however, loss of endothelial Fgfr1 and Fgfr2 results in impaired neovascularization after injury in adult mice [49••]. In addition, studies using a new allosteric FGFR inhibitor, SSR128129E, showed in a zebrafish model of vascular development that FGF signaling regulates angiogenic sprouting of the intersomitic vessels (ISV) [69•].…”
Section: Fgf Signaling In Endothelial Cells Angiogenesis and Neovasmentioning
confidence: 99%